Effectiveness of negative pressure wound healing systems applying in sternotomy after cardiac surgery: a systematic review - Christodoulou, Eleni; Vasilopoulos, Georgios; Kalogianni, Antonia; Jahaj, Edison (Health & Research Journal, 2018)
Introduction: Despite the progress of prevention and peri-operative care of cardiac surgery patients, complications of the surgical wound still occur to 1-3% of patients and they are connected with high rates of hospital mortality. Aim: The present systematic review aims to investigate the effectiveness of the application of negative pressure wound therapy in median sternotomy wounds after cardiac surgery that occur deep infections. Material and Method: All the relevant Greek and International bibliography was searched to Pubmed, Cinahl, Sciverse Scopus and Proquest database. The Key words that were used were negative pressure wound treatment AND sternotomy AND cardiac surgery regarding the pursuit of the title, the abstract or the key words for publications from 2012 and after. Results: From 123 articles, 7 articles were finally chosen for studying of the full text. According to the results of the review, negative pressure wound treatment’s use to median sternotomy wounds provide the healing, the treatment and the prevention of infections and contributes to the reduction of the time and cost of hospitalization. Conclusions: The need to carry out more randomized clinical trials is highlighted so that the results can be generalized.